2015
DOI: 10.1117/1.jbo.20.4.046002
|View full text |Cite
|
Sign up to set email alerts
|

In vivooptical microscopy of peripheral nerve myelination with polarization sensitive-optical coherence tomography

Abstract: Abstract. Assessing nerve integrity and myelination after injury is necessary to provide insight for treatment strategies aimed at restoring neuromuscular function. Currently, this is largely done with electrical analysis, which lacks direct quantitative information. In vivo optical imaging with sufficient imaging depth and resolution could be used to assess the nerve microarchitecture. In this study, we examine the use of polarization sensitiveoptical coherence tomography (PS-OCT) to quantitatively assess the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 43 publications
4
26
0
Order By: Relevance
“…20, demonstrating the reduced birefringence in tumor tissue. PS-OCT could also find an application in the study of the regeneration of nerves after injury or to visualize nerves intraoperatively during e.g., prostatectomy, due to the contrast PS-OCT images provide over structural intensity images for nerves due to their birefringent properties [171][172][173].…”
Section: Dermatology Collagen and Nerves Cartilage And The Reduced mentioning
confidence: 99%
“…20, demonstrating the reduced birefringence in tumor tissue. PS-OCT could also find an application in the study of the regeneration of nerves after injury or to visualize nerves intraoperatively during e.g., prostatectomy, due to the contrast PS-OCT images provide over structural intensity images for nerves due to their birefringent properties [171][172][173].…”
Section: Dermatology Collagen and Nerves Cartilage And The Reduced mentioning
confidence: 99%
“…OCM is a technique that capitalizes on the variation in scattering of near-infrared light between different cellular structures and tissues in order to extract contrast (Huang et al, 1991). This imaging technique has been used extensively for label-free imaging of retinal structure (Hee et al, 1995) but has also been shown to be able to extract images of myelin in the brain (Ben Arous et al, 2011;Henry et al, 2015;Yamanaka, Teranishi, Kawagoe, & Nishizawa, 2016). Similar to OCM's dependence on differential tissue scattering, THG microscopy is a nonlinear imaging approach that generates a signal at lipid-water interfaces due to nonlinear coherent scattering (Weigelin, Bakker, & Friedl, 2016).…”
Section: Label-free Myelin Imagingmentioning
confidence: 99%
“…Improved delineation of the sciatic nerve boundaries to muscle and adipose tissues as well as quantitative birefringence measurements were enabled by the additional polarization contrast [224]. In an experimental nerve crush model, decreasing birefringence was observed in parallel to a loss of myelination (Figure 12a-d) [225]. The prostatic nerves-indiscernible from surrounding tissue by standard, intensity based OCT-were identified in prostates of rats and humans, thereby indicating the feasibility of PS-OCT as a method for intrasurgical imaging [226].…”
Section: Ps-oct In Nerves and Brainmentioning
confidence: 99%